Anti-Hypoxic Molecular Mechanisms of Rhodiola crenulata Extract in Zebrafish as Revealed by Metabonomics - Ma, Yi; Wu, Yi; Xia, Zhengchao; Li, Jingyi; Li, Xiaorong; Xu, Pingxiang; Zhou, Xuelin; Xue, Ming (Frontiers in Pharmacology, 2019)
The health supplement of Rhodiola crenulata (RC) is well known for its effective properties against hypoxia. However, the mechanisms of its anti-hypoxic action were still unclear. The objective of this work was to evaluate the molecular mechanisms of RC extract against hypoxia in a hypoxic zebrafish model through metabonomics and network pharmacology analysis. A hypoxic zebrafish model in the environment with low concentration (3 %) of oxygen was constructed and used to explore the anti-hypoxic effects of RC extract, followed by detecting the changes of the metabolome in the brain through liquid chromatography-high resolution mass spectrometry. An in silico network for metabolite-protein interactions was further established to examine the potential mechanisms of RC extract, and the mRNA expression levels of the key nodes were validated by real-time quantitative PCR. As results, RC extract could keep zebrafish survive after 72-h hypoxia via improving lactate dehydrogenase, citrate synthase, and hypoxia-induced factor-1α in brains. 142 differential metabolites were screened in the metabonomics, and sphingolipid metabolism pathway was significantly regulated after RC treatment. The constructed protein-metabolites network indicated that the HIF-related signals were recovered, and the mRNA level of AMPK was elevated. In conclusion, RC extract had markedly anti-hypoxic effects in zebrafish via changing sphingolipid metabolism, HIF-related and AMPK signaling pathway.